(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2017)
Turks, along with other people of the Middle East, retain a claim to being “Caucasian”. Technically white, Turks do not fit neatly into Western racial categories especially after 9/11, and with the increasing normalization of racist discourses in Western politics, their assumed religious and geographical identities categorise “secular” Turks along with their Muslim “others” and, crucially, suggest a “non-white” status. In this context, for Turks who explicitly refuse to be presented along with “Islamists”, “whiteness” becomes an act of belonging to “the West” (instead of the East, to “the civilised world” instead of the world of terrorism). The White Turks phenomenon does not only reveal the fluidity of racial categories, it also helps question the meaning of resistance and racial identification “from below”. In dealing with their insecurities with their place in the world, White Turks fall short of leading towards a radical democratic politics.